High transmission in 120-degree sharp bends of inversion-symmetric and inversion-asymmetric photonic crystal waveguides - Wei Dai; Taiki Yoda; Yuto Moritake; Masaaki Ono; Eiichi Kuramochi; Masaya Notomi (Nature Communications)
Abstract Bending loss is one of the serious problems for constructing nanophotonic integrated circuits. Recently, many works reported that valley photonic crystals (VPhCs) enable significantly high transmission via 120-degree sharp bends. However, it is unclear whether the high bend-transmission results directly from the valley-photonic effects, which are based on the breaking of inversion symmetry. In this study, we conduct a series of comparative numerical and experimental investigations of bend-transmission in various triangular PhCs with and without inversion symmetry and reveal that the high bend-transmission is solely determined by the domain-wall configuration and independent of the existence of the inversion symmetry. Preliminary analysis of the polarization distribution indicates that high bend-transmissions are closely related to the appearance of local topological polarization singularities near the bending section. Our work demonstrates that high transmission can be achieved in a much wider family of PhC waveguides, which may provide novel designs for low-loss nanophotonic integrated circuits with enhanced flexibility and a new understanding of the nature of valley-photonics.